Asking the First Question: Reframing Bivens After Minnici - Alexander A. Reinert; Lumen N. Mulligan (Washington University Law Review, 2013)
In Minneci v. Pollard, decided in January 2012, the Supreme Court refused to recognize a Bivens v. Six Unknown Named Agents of Federal Bureau of Narcotics suit against employees of a privately run federal prison because state tort law provided an alternative remedy, thereby adding a federalism twist to what had been strictly a separation-of-powers debate. In this Article, we show why this new state-law focus is misguided. We first trace the Court’s prior alternative-remedies-to-Bivens holdings, illustrating that this history is one narrowly focused on separation of powers at the federal level. Minneci’s break with this tradition raises several concerns. On a doctrinal level, the opinion destroys Bivens’s long- established parallelism with 42 U.S.C. § 1983 actions, where suits against privately employed individuals are allowed. Additionally, it creates asymmetries between the constitutional liability faced by privately and federally employed prison employees. More significantly, it conflicts with congressional intent as expressed in the Westfall Act, which codified the Bivens remedy in 1988, by conflating two distinct questions: whether a suit requires the courts to extend Bivens jurisprudence to a new context and whether, assuming an extension is necessary, such an extension is warranted. This piece offers the only full discussion to date of the importance of this “first question” to the Bivens canon. We end this Article by offering several strategies for limiting Minneci’s impact and for returning Bivens jurisprudence to its separation-of-powers roots.
Keywords: Minneci v. Pollard; Minneci; Bivens v. Six Unknown Named Agents of Federal Bureau of Narcotics; Bivens; federalism; separation of powers; tort